Distinct Microbiomes of Gut and Saliva in Patients With Systemic Lupus Erythematous and Clinical Associations - Liu, Fengping; Ren, Tianli; Li, Xiaodi; Zhai, Qixiao; Xu, Xifeng; Zhang, Nan; Jiang, Peng; Niu, Yaofang; Lv, Longxian; Shi, GuoXun; Feng, Ninghan (Frontiers in Immunology, 2021)
Alterations in the microbiome of the gut and oral cavity are involved in the etiopathogenesis of systemic lupus erythematosus (SLE). We aimed to assess whether both microbiome compositions in feces and saliva were specific in patients with SLE. A total of 35 patients with SLE, as well as sex- and age-matched asymptomatic subjects as healthy control (HC) group were recruited. Fecal swabs and saliva samples were collected from the participants. 16S ribosomal RNA gene sequencing was performed on the samples. Compared with the HC group, reduced bacterial richness and diversity were detected in the feces of patients with SLE, and increased bacterial diversity in their saliva. Both feces and saliva samples explained the cohort variation. The feces were characterized by enrichment of Lactobacillus, and depletion of an unclassified bacterium in the Ruminococcaceae family and Bifidobacterium. Lack of Bifidobacterium was observed in patients with arthritis. Akkermansia and Ruminococcus negatively correlated with the serum levels of C3. In saliva, Veillonella, Streptococcus, and Prevotella were dominant, and Bacteroides was negatively associated with disease activity. These findings can assist us to comprehensively understand the bacterial profiles of different body niches in SLE patients.